Daniel Defoe : contrarian - Merrett, Robert James (University of Toronto Press, 2013)
In this study, Robert James Merrett approaches Defoe's body of work using interdisciplinary methods that recognize dialectic in his verbal creativity and cognitive awareness.
Keywords: Defoe, Daniel, -- 1661?-1731 -- Criticism and interpretation.; Defoe, Daniel, -- 1661?-1731 -- Psychology.; Defoe, Daniel, -- 1661?-1731; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Psychology; Criticism, interpretation, etc.